Analysis of the influence of transformational leadership, cohesion and work motivation in improving employee performance - Diana Hasan; Rudy Sunardi; Gusti Anissa; Rini Fatma Kartika; Yuliana Saridewi Kusumastuti (Dinasti International Journal of Education Management and Social Science, 2026)
Performance challenges in the public sector often translate into job demands that require a high degree of individual innovation. Similarly, the Islamic banking industry is also facing increasing pressures to continuously enhance employee performance. This study aims to analyze the influence of transformational leadership, work motivation, and group cohesion on employee performance, with the goal of developing a new conceptual model that can serve as a reference for practitioners in the Islamic banking sector, particularly in Indonesia. Data were collected through a structured questionnaire distributed via Google Forms. A purposive sampling technique was applied to select respondents from several Islamic banks across Indonesia, resulting in 350 valid responses that met the predefined criteria. The data were then analyzed using SmartPLS 4. The results indicate that work motivation exerts no significant impact on employee performance. Likewise, transformational leadership is found to have no direct effect on employee performance. However, transformational leadership has a strong and positive effect on group cohesion, which, in turn, significantly influences employee performance. Among the variables tested, the path from transformational leadership to cohesion showed the strongest effect. These results suggest that the impact of transformational leadership on employee performance is more effective when mediated by cohesion. The study concludes that fostering a cohesive work environment enhances the positive effects of transformational leadership on performance outcomes. The implications of this research provide valuable insights for Islamic banking leaders, emphasizing the importance of adopting a transformational leadership style while simultaneously fostering team cohesion to optimize employee and organizational performance.